On the accuracy of hiding information metrics: counterfeit protection for education and important certificates - Hmood, A.K.; Kasirun, Zarinah Mohd; Jalab, Hamid Abdullah; Alam, Gazi Mahabubul; Zaidan, A.A.; Zaidan, B.B. (Academic Journals, 2010)
There are two techniques used to hide information - one is steganography while the other is digital watermarking. The objective of this paper is to investigate the functionality and reliability of using the current metrics, which are used to measure the distortion caused by secret data embedding. These metrics are used to measure the quality of the steganographic or watermarked objects. The signal-to-noise ratio, peak signal-to-noise ratio, mean square error, root mean square error, histogram and human vision test are the current measurements for the steganographic object. The paper will also discuss the widely used metrics and their limitations. Apart from this, it will also look at how researchers have criticized the metrics and how these metrics are used to measure the quality of steganographic or watermarked objects.